Avoidance of sponsored posts on consumer-generated content: a study of personal blogs - Mutum, Dilip S.; Ghazali, Ezlika Mohd; Mohd-Any, Amrul Asraf; Nguyen, Bang (Emerald, 2018)
Purpose: This study aims to conceptualise and empirically examine how blog users engage with the sponsored posts on consumer-generated content, specifically blogs. Design/methodology/approach: This paper empirically tested the proposed hypotheses using the structural equation modelling using a sample of 399 blog users. Findings: The need for cognition, perceived interactivity and perceived credibility of blogs has been found to directly influence consumers’ attitude towards blogs. Innovativeness has been found to have a weak negative link with the attitude towards blogs. Blog users were more favourable towards the sponsored posts if the blogs were more interactive. Attitude towards blogs has been found to mediate the relationship between users’ perceived interactivity and their avoidance of the sponsored posts and also between perceived credibility and avoidance of the sponsored posts on blogs. The most significant finding of this study is that the positive attitude towards a blog results in a higher avoidance of the sponsored posts. Research limitations/implications: This study focuses on the sponsored posts on blogs. It does not look at other forms of advertising on blogs such as banner ads, or other forms of consumer-generated content. Practical implications: Marketers and bloggers should carefully consider the suitability of the sponsored posts on blogs as they risk alienating the regular users of the blogs. Sponsored posts which are perceived as honest reviews (as opposed to paid advertorials) might be more acceptable to blog users. Social implications: This study highlights the importance of credibility of bloggers to blog users. There are some serious ethical issues related to the sponsored posts which have not been discussed here but need to be examined further. Originality/value: This study represents one of the first attempts to conceptualise and empirically examine how blog users engage with customer-generated advertising – sponsored posts. It contributes to marketing literature by enhancing the understanding of how consumers perceive consumer-generated content and more specifically, with regard to consumer attitudes towards online consumer-generated advertising. This study enhances the theoretical and empirical knowledge on how consumers react to advertisements on social media, with important suggestions for future research and implications for practitioners.